Technical feasibility study model of aged apartment renovation applying analytic hierarchy process - Choi, Junho; Choi, Jaepil (Journal of Civil Engineering and Management, 2022)
Residential buildings are being renovated around the world, especially apartments, their solutions are becoming increasingly important. The number of apartments in Korea that are more than 20 years old has reached 4.3 million, and the problem of aged apartments now needs to be addressed. Consequently, the government is promoting the improvement of the residential environment through renovation. In a renovation project, a feasibility study is conducted at the outset, but many apartments fail to complete the renovation process during the project. One reason is that feasibility studies focus on economics without sufficiently considering the technical aspects of the redesign. This study developed a feasibility study model that can pre-evaluate apartment renovation in terms of technology. We selected 27 criteria that affect technical feasibility, and the analytic hierarchy process (AHP) was performed with experts to derive the relative importance of the criteria. Based on the weight of the criteria, we developed an apartment renovation technology feasibility study model. As a result of the study, unit and complex conditions were found to have a significant influence on renovation. Moreover, it was found that the technical feasibility study model can quantitatively evaluate the technical aspects of an apartment to be renovated.First published online 30 December 2021